2016
DOI: 10.1007/s00246-016-1479-3
|View full text |Cite
|
Sign up to set email alerts
|

Speckle-Tracking Echocardiographic Measures of Right Ventricular Diastolic Function Correlate with Reference Standard Measures Before and After Preload Alteration in Children

Abstract: Background The accuracy of echocardiographic measures of right ventricular (RV) diastolic function has been sparsely studied. Our objective was to evaluate the correlation between echocardiographic and reference standard measures of RV diastolic function derived from micromanometer pressure analysis before and after preload alteration in children. Methods Echocardiograms and micromanometer pressure analyses were prospectively performed before and after fluid bolus in children undergoing right heart catheteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several other studies on adult patients have also demonstrated pre‐load conditions must be accounted for when evaluating diastolic function by mitral valve inflow velocities 7,17 . We are aware of only one pediatric study utilizing pre‐load alteration to help evaluate diastolic function in the cardiac catheterization lab, but the authors focused on right ventricular hemodynamics, without assessments of LVEDP or PCWP 11 . In our cohort, cardiac catheterization measures of diastolic function (LVEDP or PCWP) were normal, then increased significantly to abnormal values following pre‐load alteration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several other studies on adult patients have also demonstrated pre‐load conditions must be accounted for when evaluating diastolic function by mitral valve inflow velocities 7,17 . We are aware of only one pediatric study utilizing pre‐load alteration to help evaluate diastolic function in the cardiac catheterization lab, but the authors focused on right ventricular hemodynamics, without assessments of LVEDP or PCWP 11 . In our cohort, cardiac catheterization measures of diastolic function (LVEDP or PCWP) were normal, then increased significantly to abnormal values following pre‐load alteration.…”
Section: Discussionmentioning
confidence: 99%
“…7,17 We are aware of only one pediatric study utilizing pre-load alteration to help evaluate diastolic function in the cardiac catheterization lab, but the authors focused on right ventricular hemodynamics, without assessments of LVEDP or PCWP 11. In our cohort, cardiac cathe-e′> 10 was associated with an abnormal PCWP 15,16.…”
mentioning
confidence: 93%
See 2 more Smart Citations